If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14a + -3b + -4a + b = 0 Reorder the terms: 14a + -4a + -3b + b = 0 Combine like terms: 14a + -4a = 10a 10a + -3b + b = 0 Combine like terms: -3b + b = -2b 10a + -2b = 0 Solving 10a + -2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. 10a + -2b + 2b = 0 + 2b Combine like terms: -2b + 2b = 0 10a + 0 = 0 + 2b 10a = 0 + 2b Remove the zero: 10a = 2b Divide each side by '10'. a = 0.2b Simplifying a = 0.2b
| 6x-4x+3x-y+2y= | | 0.03-0.02(x+1)=-0.01(2-x) | | 2x*4=6x | | 2(2n+4)=7(4n+5)+4 | | c(3.10)=300+0.92(3.10) | | c(x)=300+0.92x | | 3y+z=10 | | 2000+3r= | | -3-8/15+-8= | | 2x-z=8 | | 50-18x^2=0 | | 2x-3/5--4= | | -12k^2+20k+57=0 | | 7(a+x)=49 | | -12k^2+20k+39=0 | | a(b-3)=4 | | 109-4x=32x+17 | | =31 | | 4a^2-5b+1=0 | | 20k^2-44k-39=0 | | 0-4x=12-7 | | 27-6=11 | | 2y-4=-11+3y | | 4x-6=4(x-2) | | 2y-4=11-3y | | 8x-7=-5x-16 | | (x/2+1)^2-1=x^2-1 | | 19-2(3x-1)/5=x+3 | | 8x-7=5x+16 | | 19-2(3x-1)/5=x+5 | | -114-8x=11-8(x)(x) | | 3(x)(x)+7x-4=11x |